Design of interactive learning courseware for graph search algorithms - Ng, Jone Kan (Nanyang Technological University, 2020)
The advancement in technology through the years has given rise to E-learning becoming a supplement or even a substitute for face-to-face classes. With the possible immersive and interactive content able to be created and used in learning, E-learning is widely implemented by schools and educational institutions to hold lessons and deliver learning content. The convenience of place and time offered by E-learning allows learners to have the flexibility of learning from any location at any time – especially important when unable to attend a lesson in time or being restricted from travelling, such as during a pandemic.